Interaction of SERINC5 and IFITM1/2/3 regulates the autophagy-apoptosis-immune network under CSFV infection. Issue 1 (31st December 2022) - Li, Wenhui; Zhang, Zilin; Zhang, Liangliang; Zhou, Qingfeng; Li, Yuwan; Yi, Lin; Ding, Hongxing; Zhao, Mingqiu; Chen, Jinding; Fan, Shuangqi
ABSTRACT: The host restriction factor serine incorporator 5 (SERINC5) plays a key role in inhibiting viral activity and has been shown to inhibit classical swine fever virus (CSFV) infection. However, the action of SERINC5 in the interaction between host cells and CSFV remains poorly understood. This study found that SERINC5 represses CSFV-induced autophagy through MAPK1/3-mTOR and AKT-mTOR signalling pathways. Further research showed that SERINC5 promotes apoptosis by repressing autophagy. Likewise, it was demonstrated that SERINC5 interacting proteins IFITM1/2/3 inhibit CSFV replication and regulate autophagy in a lysosomal-associated membrane protein LAMP1-dependent manner. In addition, IFITM1/2/3 interference promotes the NF-κB signalling pathway for potential immunoregulation by inhibiting autophagy. Finally, the functional silencing of IFITM1/2/3 genes was demonstrated to enhance the inhibitory effect of SERINC5 on autophagy. Taken together, These data uncover a novel mechanism through SERINC5 and its interacting proteins IFITM1/2/3, which mediates CSFV replication, and provides new avenues for controlling CSFV.